2023
DOI: 10.1038/s41419-023-05611-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of H3K9/H3K14 acetylation by small molecules drives neuron-fate-induction of glioma cell

Abstract: Differentiation therapy using small molecules is a promising strategy for improving the prognosis of glioblastoma (GBM). Histone acetylation plays an important role in cell fate determination. Nevertheless, whether histone acetylation in specific sites determines GBM cells fate remains to be explored. Through screening from a 349 small molecule-library, we identified that histone deacetylase inhibitor (HDACi) MS-275 synergized with 8-CPT-cAMP was able to transdifferentiate U87MG GBM cells into neuron-like cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Our results also strongly suggest that combinatorial treatment with QST and IR not only represses genes involved in cellular proliferation but also induces genes involved in neuronal signaling in vivo. In line with our observations, 2 recent studies in preclinical models of DIPG (with the bifunctional LSD1/HDAC inhibitor Corin) and GBM (with the small molecule MS-275) demonstrated that HDAC inhibition induces the expression of genes related to neuronal differentiation in vitro and in vivo ( 56 , 57 ). Whether this shift toward neuron-like cell fate represents an induction of differentiation phenotype or a potential means to evade cell death remains an open question.…”
Section: Discussionsupporting
confidence: 90%
“…Our results also strongly suggest that combinatorial treatment with QST and IR not only represses genes involved in cellular proliferation but also induces genes involved in neuronal signaling in vivo. In line with our observations, 2 recent studies in preclinical models of DIPG (with the bifunctional LSD1/HDAC inhibitor Corin) and GBM (with the small molecule MS-275) demonstrated that HDAC inhibition induces the expression of genes related to neuronal differentiation in vitro and in vivo ( 56 , 57 ). Whether this shift toward neuron-like cell fate represents an induction of differentiation phenotype or a potential means to evade cell death remains an open question.…”
Section: Discussionsupporting
confidence: 90%
“…[18][19][20] H3K9 acetylation is closely associated with the activation of immune-related genes, and the acetylation of H3K9/K14 often marks actively transcribed genes, with potential implications for therapeutic outcomes. 34 H3K27 acetylation plays a role in immune cell modulation and responses to cancer therapy. [35][36][37] A study by LaMere et al provides insights into the role of H3K27 acetylation in T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we selected H3 acetylation at sites K9, K9/K14 and K27 for evaluation due to their clinical relevance in the context of immune responses, antitumour effects and gene regulation 18–20 . H3K9 acetylation is closely associated with the activation of immune‐related genes, and the acetylation of H3K9/K14 often marks actively transcribed genes, with potential implications for therapeutic outcomes 34 . H3K27 acetylation plays a role in immune cell modulation and responses to cancer therapy 35–37 .…”
Section: Discussionmentioning
confidence: 99%
“…MS-275, another HDAC inhibitor, decreases cell proliferation and induces the differentiation of human dental pulp stem cells into odontoblast-like cells [ 8 ] and human mesenchymal stem cells [ 1 ]. MS275 also has been known to differentiate U87MG glioblastoma multiforme cells into neural cells when it synergized with 8-CPT-cAMP [ 47 ]. Another HDAC inhibitor, VPA, has been known to effective inducer of differentiation.…”
Section: Discussionmentioning
confidence: 99%